'Can't be what you can't see' : the transition of Aboriginal and Torres Strait Islander students into higher education : literature review 2014. - Wilks, Judith; Wilson, Katie (Australia. Office for Learning and Teaching, 2014)
This literature review examines relevant research, policy and programs in peer-reviewed, non-peer-reviewed and grey literature relating to the transitioning of Aboriginal and Torres Strait Islander Australians into higher education, including case studies of promising practice models nationally and internationally. It reviews information in relation to the key enablers, constraints, knowledge gaps, and current initiatives to support under-represented groups, strategies to assist potential students to transition successfully into higher education, and best practice examples for deeper analysis of factors affecting Aboriginal and Torres Strait Islander transition to Australian universities. [Introduction, ed]